SMARTPHONE RECOMMENDATION SYSTEM USING MODEL-BASED COLLABORATIVE FILTERING METHOD - Fajar Aji Prayoga; Kusnawi Kusnawi (Informatika, Universitas Jenderal Soedirman, 2022)
Smartphone are now an importan item that is needed by many people. The rapid development of technology make smartphone companies are competing to release their best smartphones.The many smartphones in online shop cause user to become disoriented about their choice. A recommendation system can help the user in choosing the smartphone that the user likes. In this study, a recommendation system was made using the collaborative filtering method with the K-Nearest Neighbors algorithm and combined with the application of K-Means algorithm to divide the smartphone into several group. The output of collaborative filtering method is that the model can give smartphone rating predictions to user. The prediction results will be used as the basis for giving recommendations to user. The purpose of smartphones groupping is so that the recommendation results are more specific and accurate. The evaluation of the model gets an MAE value is 1.1047 and RMSE value is 1.7579. So it can be concluded that the development of a smartphone recommendation system was successfully implemented.